2020
DOI: 10.1136/jitc-2020-000862
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection in immunocompromised patients: humoral versus cell-mediated immunity

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic placed unprecedented pressure on various healthcare systems, including departments that use immunotherapies such as chimeric antigen receptor (CAR) T-cell therapy and immunosuppression therapy in organ transplantation units. The true impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on immunocompromised CAR T-cell therapy recipients and kidney transplant recipients (KTRs) has not yet been established.Case presentationIn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…Immunocompromised patients infected with SARS-CoV-2, especially those with comorbidities, may have a higher risk for severe outcomes than the general population [6][7][8]. Individuals with autoimmune diseases have an increased risk for infections [9,10].…”
Section: Key Pointsmentioning
confidence: 99%
“…Immunocompromised patients infected with SARS-CoV-2, especially those with comorbidities, may have a higher risk for severe outcomes than the general population [6][7][8]. Individuals with autoimmune diseases have an increased risk for infections [9,10].…”
Section: Key Pointsmentioning
confidence: 99%
“…If the PCR test result is positive, surgery should be postponed until at least 2 weeks after COVID-19 symptom. Wei et al [ 17 ] reported two immunocompromised patients with severe COVID-19 pneumonia. One patient generated specific anti-immunoglobulin G antibodies of SARS-CoV-2 after 2 weeks of treatment, and could discharge from the hospital on day 42.…”
Section: Introductionmentioning
confidence: 99%
“…One patient generated specific anti-immunoglobulin G antibodies of SARS-CoV-2 after 2 weeks of treatment, and could discharge from the hospital on day 42. However, the other failed to obtain specific antibodies of SARS-CoV-2, and eventually died due to respiratory failure [ 17 ]. In immunocompromised patients, the surgery may need to be postponed for longer (at least 24 days), because the time to clear SARS-CoV-2 tends to be longer [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…impairment, such as that resulting from cancer, has been associated with prolonged SARS-CoV-2 shedding and the seeding of "super-spreader" events [14][15][16][17][18]. As we consider host-directed small molecules as candidates for antiviral therapies, it remains critically important to assess their impact on both dependency factors and restriction factors before they are deployed to slow virus transmission and/or prevent viral pathogenesis in humans.…”
mentioning
confidence: 99%